NEW EMERGING TRENDS IN BANKING SECTOR IN INDIA - Saxena, Dr Kavita (Innovative Research Thoughts, 2017)
The banking industry is critical to a country's economic growth. Banks' success relies on their ability to meet the needs of its clients in a variety of ways. Recent economic changes in India have highlighted the rising importance of banking services. Any nation that has a well-regulated banking system provides a level of comfort to both local and foreign investors. One of the reasons India was spared the worst effects of the global financial crisis is attributed to its strict banking regulations. Commercial Banks and Co-operative Banks are both types of banks. Those banks that satisfy certain requirements are listed in the second schedule of the RBI Act, 1934. This kind of bank is known as a scheduled one. Commercial banks and cooperative banks both fall within this category. The Reserve Bank of India considers scheduled banks to be more secure, and as a result, they are granted additional privileges including re-financing. Inclusion in the schedule also entails reporting to the RBI and keeping a proportion of its demand and time obligations as Cash Reserve Ratio (CRR) with the RBI as part of its duties.